“Nobody cared about us”: Navigating the quest for academic success in Oaxaca, Mexico (Polis (Santiago), 2021)
Access to higher education, and success once there, depends on many variables. In this article, I unpack the major obstacles low income and indigenous high school and college students perceive that they face in Oaxaca de Juárez, Mexico. In combination with a structural analysis of the context of Oaxaca based in comparative historical literature, I use political ethnography and qualitative interviews to situate testimonies from recent high school and college graduates about their schooling experiences and obstacles they face in the quest for academic and professional success. I document the matrix of obstacles students name in their educational pathways, including financial resources, mental health, motivation, Oaxacan political instability, physical insecurity, hostile school climates, and discrimination against indigenous people. I draw on the case study of a non-governmental academic support organization, the Institute for Community Integration and Counseling (IIAC), based in Oaxaca de Juárez, Mexico.
Keywords: Education; obstacles; Oaxaca; México; interventions.